Modelling the kinetics of biomass and lactic acid production during Rohu fish pickle fermentation / Arjun Ghimire and Stuti Sapkota - Ghimire, Arjun; Sapkota, Stuti (Universiti Teknologi MARA, 2020)
Drying is generally used to increase the shelf life of food products. In this context, mango fruit is used as a sample for the drying process because of its high commercial value and particularly high moisture content. The mango was sliced into few batches of sample with a size of 20 mm × 30 mm × 5 mm each. The experiments were conducted using tray and oven dryer at different temperatures of 40, 50 and 60 °C with a steady airflow rate of 1.3 m/s. The objectives are to study the effect of drying time, temperature and air velocity towards drying of mango fruit, to compare the physical characteristics of mango sample after drying and to determine the best drying kinetics model fitted to each tray and oven dryer. The results showed that the increase in drying time, temperature and air velocity would reduce the moisture content while at the same time, drying rate increased significantly. Tray dryer was found to be more effective than oven dryer because of higher drying rate with better product quality and appearance at the end. Furthermore, the gathered data were fitted into few widely used drying mathematical models and it was found that Henderson and Pabis model at 60°C is best suited for tray dryer whereas Page model at 40 °C is the best for oven dryer